Jejak Islamisasi di Bekasi dalam Perspektif Sejarah - Adam, Yusril Fahmi; Badrun, Badrun; Muhammad, Firza Nofdi (Faculty of Ushuluddin, Adab, and Da'wah, State Islamic University of Palangkaraya, 2023)
This article aims to explore Islamization in Bekasi from a historical perspective. This article uses the historical method, anthropological approach, and cultural diffusion theory to analyze the issue. Using these methodologies, this research will be narrative-descriptive and analytical-descriptive. This study found that Islamization in Bekasi occurred for the first time when Falatehan occupied Sunda Kelapa and turned into Jayakarta in 1527, which impacted the entry of Islam into Bekasi. However, the massive Islamization process could only be carried out in the 20th century when KH Ma'mun Nawawi and KH Noer Ali played a role in preaching Islam in Bekasi. Both of them were also members of the Betawi ulama network in the 20th century. This study concludes that Islamization in Bekasi has taken a long time because Bekasi differs from Karawang and Jayakarta, both international trade centres, while Bekasi is only a passageway. Regardless, Bekasi remains a significant place for the Nusantara trade route.Keywords: